Systematic construction of exact magnetohydrodynamic models for astrophysical winds and jets - Vlahakis, N.; Tsinganos, K. (1998)
By a systematic method we construct general classes of exact and self-consistent axisymmetric magnetohydrodynamic (MHD) solutions describing flows that originate in the near environment of a central gravitating astrophysical object. The unifying scheme contains two large groups of exact MHD outflow models: (I) meridionally self-similar models with spherical critical surfaces; and (II) radially self-similar models with conical critical surfaces. This classification includes known polytropic models, such as the classical Parker description of a stellar wind and the Blandford &38 Payne model of a disc wind; it also contains non-polytropic models, such as those of winds/jets in Sauty &38 Tsinganos, Lima, Tsinganos &38 Priest, and Trussoni, Tsinganos &38 Sauty. Besides the unification of all known cases under a common scheme, several new classes emerge and some are briefly analysed; they could be explored for a further understanding of the physical properties of MHD outflows from various magnetized and rotating astrophysical objects in stellar or galactic systems.
Keywords: Astrophysics; galaxies: jets; ISM: jets and outflows; MHD; solar wind; stars: atmospheres; stars: mass-loss